Factors in Science Journal Cancellation Projects: The Roles of Faculty Consultations and Data. - Jeanine Williamson; Peter Fernandez; Lana Dixon (Issues in Science and Technology Librarianship)
The economic downturn of 2007-08 forced many academic libraries in the United States to cancel journals. We surveyed life sciences librarians from ARL libraries to find out about their experiences with journal cancellations during 2008-12. Overall, we discovered that two factors were essential in decision-making: faculty consultations and data. While faculty consultations and data have always been influential in journal cancellations, our survey allowed us to explore what roles these two factors played in the recent period of necessary reductions. [ABSTRACT FROM AUTHOR]